Cephalexin-mediated synthesis of quasi-spherical and anisotropic gold nanoparticles and their in situ capping by the antibiotic - Jagannathan, Ramya; Poddar, Pankaj; Prabhune, Asmita (Journal of Physical Chemistry C, 2007)
Here we report, for the first time, synthesis of gold nanostructures in aqueous medium by reducing gold ions using cephalexin, a potent broad-spectrum antibiotic, where the morphology of the gold nanoparticles is found to be dependent on the concentration of chloroauric acid. The characterization techniques indicate that particle surfaces are coated with the robust layer of the antibiotic making them stable for a long time. Thus, cephalexin acts as both the reducing and the capping agent. NMR and XPS analysis indicate that the sulfur moiety is responsible for the reduction and binding process.